Feasibility study for a THz acceleration experiment on the PHIL accelerator at LAL. (July 2020) - Vinatier', T; Bruni, C; Assmann, R W; Dorda, U; Lemery, F; Marchetti, B
Abstract: We present a feasibility study for an experiment aiming to post-accelerate an electron bunch, coming from the PHIL (Photo-Injecteur au LAL) photoinjector at LAL (Laboratoire de l'Accélérateur Linéaire), in a circular partially dielectric-loaded waveguide (DLW) driven by a multicycle THz pulse generated by the infrared laser coming from the LASERIX (Installation laser XUV/IR de l'Université Paris Sud) facility. We first discuss the considerations taken into account to fix the DLW design and the THz pulse properties, especially the choice of a 160 GHz THz pulse frequency, and then provide a set of values for their main parameters. We then perform start-to-end simulations of the acceleration experiment, taking into account the current achievable range of parameters at PHIL and the THz pulse properties already achieved with LASERIX with some margins for the coupling losses. They demonstrate the possibility to obtain a 1.2 MeV energy gain for a 10 pC bunch, without charge losses, with a clear shift of the energy spectrum, which would represent a significant improvement compared to the current state-of-the-art of THz acceleration. An overview of the upcoming steps towards the realization of the experiment is finally given.